DELIGNIFIKASI TANDAN KOSONG KELAPA SAWIT (TKKS) DENGAN NaOH TERHADAP KUALITAS PUPUK ORGANIK CAIR - Aulia, Winda Dwi; Permana, Asep Tata; Dimawarnita, Firda; Faramitha, Yora (Jurnal Teknologi Industri Pertanian, 2024)
Empty palm oil bunches (EFB) are the largest solid waste produced in every processing of palm oil and need to be utilized so as not to pollute the environment. One effort that can be made is to process EFB into liquid fertilizer. However, the high lignin content in EFB makes it difficult for this waste to decompose naturally. Therefore, efforts need to be made to reduce lignin levels in EFB with a delignification process for two hours at a temperature of 90 oC with 12% NaOH solution. The aim of this research was to evaluate the effect of delignification on the quality of liquid fertilizer (N, P, K, Ca, Mg, S, fulvic acid, C/N ratio, and pH). This study used a completely randomized design (CRD) with four treatments and five replications. P1: Non-delignified EFB, P2: P1 + cow urine, P3: delignified EFB, and P4: P3 + cow urine. Liquid fertilizer was made using a fermentation method for 21 days. The research results showed that delignification treatment was able to increase the presence of calcium and magnesium in liquid fertilizer. The combination of delignification with the addition of cow urine increases the availability of fulvic acid in liquid fertilizer. Keywords: empty palm oil bunches, lignin, nutrients, waste